THE EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT (GRDP), CAPITAL EXPENDITURE, AND UNEMPLOYMENT RATE ON POVERTY IN TANAH DATAR REGENCY - Adib; Mutiara Lailatussubha (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Poverty remains one of the major development challenges faced by many regions, including Tanah Datar Regency. This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), capital expenditure, and open unemployment rate on poverty in Tanah Datar Regency during the period 2010–2024. The study employs a quantitative approach using multiple linear regression analysis. The data used are secondary time-series data obtained from the Central Statistics Agency (BPS) of Tanah Datar Regency and West Sumatra Province. The results indicate that GRDP has a negative and significant effect on poverty, with a coefficient value of -0.000450 and a probability value of 0.0006. This finding suggests that increased regional economic activity contributes to poverty reduction through higher income and improved welfare. Meanwhile, capital expenditure has a negative but insignificant effect on poverty, with a probability value of 0.7535. Similarly, the open unemployment rate shows a negative but insignificant effect, with a probability value of 0.5044. Overall, the study concludes that GRDP is the most influential factor in reducing poverty in Tanah Datar Regency, while capital expenditure and the open unemployment rate do not exhibit significant effects during the study period.